Perkembangan Sistem Pendidikan di Korea Selatan (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
This article is entitled "Development of the Education System in South Korea". This article was written with the aim of analyzing and clarifying the comparison of the Korean and Indonesian curricula in more detail. The type of research used in this research is library research. The data source for this research is a journal or scientific article. This research uses data and information collection methods using technology in the form of computers and various library and internet sources such as books, magazines, articles and similar research results. The aim of this research is to consider methods and steps that can be taken to improve the quality of education through comparative educational analysis research. This research shows that there are differences between the two countries, namely in their curriculum. The Korean curriculum focuses on providing students with skills that prepare them to enter the world of work. On the other hand, the Indonesian curriculum focuses on responding to the challenges of the 4.0 revolution era. Therefore, considering that there are still many unresolved unemployment problems in Indonesia, Indonesia needs to emulate several Korean education curricula, especially to prepare students to be ready to enter the world of work.